Ammonium Cycling and Nitrification Stimulation during Oil Sludge Remediation by Gram-Positive Bacteria Lysinibacillus sphaericus Using Red Wiggler Earthworm Eisenia fetida - Juan Diego Acevedo; Jenny Dussán (AgriEngineering, 2020)
The performance of a mixture between L. sphaericus and E. fetida was evaluated for ammonium cycling and nitrifying bacteria stimulation during oil sludge remediation. The addition of E. fetida significantly increased ammonium concentration (p = 0.0218) and total Colony-forming units (CFU) count p = 0.02848). However, oil sludge with worms and L. sphaericus reached lower ammonium concentrations and CFU counts than sludge with worms alone. Sludge inoculated only with L. sphaericus presented higher ammonium concentration than sludge without inoculum, but the bacterial population reached a lower density during the final days. Final DNA and RNA extractions from all treatments amplified for L. sphaericus putative amoA and Gram-negative nitrifying bacteria amoA genes correlated with diminished ammonium concentrations during the final days of the experiment. Final RNA extractions for L. sphaericus amplified for Molybdenum transporter gene suggesting possible nitrogen fixation by L. sphaericus. The addition of Red Wiggler Earthworm to oil sludge remediation systems may provide better conditions for bacterial populations to carry out hydrocarbon degradation. The addition of E. fetida to a L. sphaericus crude oil biodegradation system may improve soil ammonium concentrations and nitrifying activity, and this could be crucial in oil sludge remediation because of bacterial inhibition due to high C:N ratios. The final product of this process may be used for soil enhancement due to its richness in nutrients and beneficial bacterial populations.